Comparison of emotional components, chronic fatigue and sleep quality in patients with rheumatoid arthritis and healthy people - Shafigheh Yousefi; Zahra Zanjani; Batol Zamani; Abdolah Omidi; Mansur Sayyah (Fiyz̤, 2021)
Background: Rheumatoid arthritis (RA) is an inflammatory disease involving small and large joints. In addition to physical problems and physical disabilities, this disease has social and psychological consequences such as depression, anxiety and lack of a purposeful life. This study aimed to compare the emotional components, chronic fatigue and sleep quality in healthy individuals and patients with rheumatoid arthritis. Materials and Methods: In this case-control study, 40 patients with rheumatoid arthritis referred to the office of rheumatologists in Kashan and 40 healthy individuals were purposefully selected. The research instruments included the Anxiety, Stress, Depression (Depression Anxiety Stress Scale), Chronic Fatigue Scale and Pittsburg Sleep quality index questionnaires. Data analysis was performed using SPSS software version 22 with Mann-Whitney U test and independent t-test. Results: The results showed that the level of emotional components and chronic fatigue in the rheumatoid arthritis group was significantly higher than the healthy group (P<0.001) and the rheumatoid arthritis group had a lower quality of sleep (higher score) than the healthy group (P<0.001), also. Conclusion: According to the findings of the present study, it can be said that the rate of anxiety, depression, stress and chronic fatigue in patients with rheumatoid arthritis are high and have low sleep quality, also. Given that many joint pains may be of non-organic origin in these patients, it is recommended to pay more attention to the psychological aspects of these patients and their treatment.